2016
DOI: 10.1590/s1806-37562016000000152
|View full text |Cite
|
Sign up to set email alerts
|

Choosing wisely between randomized controlled trials and observational designs in studies about interventions

Abstract: (SP) Brasil. 2. Methods in Epidemiologic, Clinical and Operations Research-MECOR-program, American Thoracic Society/Asociación Latinoamericana del Tórax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…In contrast, studies with a small sample, as evidenced in the study in which one of the CTs reported only having one subject enrolled, may lead to bias in the representativeness of the analysis. Randomization of eligible participants in intervention or control groups is another important point in this type of study, since it is a way of guaranteeing the same chance of allocation for both groups (23)(24) .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies with a small sample, as evidenced in the study in which one of the CTs reported only having one subject enrolled, may lead to bias in the representativeness of the analysis. Randomization of eligible participants in intervention or control groups is another important point in this type of study, since it is a way of guaranteeing the same chance of allocation for both groups (23)(24) .…”
Section: Discussionmentioning
confidence: 99%
“…39 Treatment randomizations may be useful in helping avoid key sources of bias, such as selection bias and imbalance in baseline risk factors, by randomly allocating patients to treatment or control, a technique that lends itself to use in registries and health systems or as a stand-alone approach. 60 The TASTE (Thrombus Aspiration in ST-Elevation Myocardial Infarction) randomized registry trial, for example, randomized patients from an existing registry, substantially lowering the cost of patient recruitment and speeding time to completion since the data of interest were already being collected as part of the registry protocol. 61 Similarly, the Diuretic Comparison Project by the US Veterans Administration is a switching study where participants who were using hydrochlorothiazide diuretics, 25 or 50 mg daily, were randomized at the point of care (here, the pharmacy) to either stay on their current regimen or switch to chlorthalidone at a suggested equipotent dose.…”
Section: Dovepressmentioning
confidence: 99%
“…Os ganhos potenciais com este tipo de disseminação são muito significativos. Não somente relacionados a uma melhor formação dos pesquisadores, mas também no aumento da capacidade crítica do leitor de uma forma geral, o que pode ao longo do tempo servir como mecanismo de pressão para o aumento na qualidade da ciência disponível.Para ressaltar especificamente o que tem sido feito no JBP, (5) há quatro anos iniciou-se a publicação da série de educação continuada em metodologia científica, abordando os mais diversos temas relacionados à estruturação de um projeto de pesquisa (4,(6)(7)(8) até a interpretação adequada dos diferentes tipos de estudo (9)(10)(11) . Estamos agora pesquisando qual o impacto que a publicação desta série de artigos teve para os leitores do jornal, mas de uma forma geral ela já serve como ponto de referência para os pesquisadores da área.Mas mesmo este tipo de iniciativa representa pouco em relação à dimensão do problema.…”
unclassified